Withdrawal of dietary phytoestrogens in adult male rats affects hypothalamic regulation of food intake, induces obesity and alters glucose metabolism. (5th February 2015) - Andreoli, María Florencia; Stoker, Cora; Rossetti, María Florencia; Alzamendi, Ana; Castrogiovanni, Daniel; Luque, Enrique H.; Ramos, Jorge Guillermo
Highlights: Phytoestrogen withdrawal in the adult stage of life induced obesity in male rats. Obesity was associated to hyperphagia with altered hypothalamic regulation of food intake. Glucose homeostasis was impaired, manifested by insulin resistance and diabetes. Phytoestrogen withdrawal led to greater obesity and diabetes than a high fat diet. Abstract: The absence of phytoestrogens in the diet during pregnancy has been reported to result in obesity later in adulthood. We investigated whether phytoestrogen withdrawal in adult life could alter the hypothalamic signals that regulate food intake and affect body weight and glucose homeostasis. Male Wistar rats fed from conception to adulthood with a high phytoestrogen diet were submitted to phytoestrogen withdrawal by feeding a low phytoestrogen diet, or a high phytoestrogen–high fat diet. Withdrawal of dietary phytoestrogens increased body weight, adiposity and energy intake through an orexigenic hypothalamic response characterized by upregulation of AGRP and downregulation of POMC. This was associated with elevated leptin and T4, reduced TSH, testosterone and estradiol, and diminished hypothalamic ERα expression, concomitant with alterations in glucose tolerance. Removing dietary phytoestrogens caused manifestations of obesity and diabetes that were more pronounced than those induced by the high phytoestrogen–high fat diet intake.